VALERIAN EXTRACT USED AS POTENTIAL CORROSION INHIBITOR FOR CARBON STEEL IN DIFFERENT MEDIA - DIMA, George-Daniel; ȘERBOIU, Oana-Tabita; DAN, Mircea Laurențiu; COSTEA, Liviu-Virgil (Studia Universitatis Babeș-Bolyai Chemia, 2023)
The paper investigates the corrosion inhibition property of the Valerian (Valeriana officinalis) extract for carbon steel in acid and neutral solutions. The extracted natural compounds from plants have been reported in the literature as efficient corrosion inhibitors due to their stability to different environments, eco-friendly character, and their low cost. The usefulness of a different type of valerian species, in corrosion protection, by inhibiting the anodic oxidation reaction due to the improvement of the development of a passivating film, has been reported earlier for the Valeriana wallichii root extract in the corrosion of mild steel in different acidic media. Based on the latter findings, our studies have been performed in three different media, H2SO4, HCl and NaCl. An array of electrochemical techniques such as Tafel polarization, cyclic voltammetry, as well as chronopotentiometry have been employed to elucidate the corrosion behavior of carbon steel within the investigated media, containing various amounts of Valeriana officinalis extract. Quantum chemical calculations have been employed in order to assess the adsorption capacity of the mentioned extract onto the metal surface. The latter extract exhibits inhibitory effects in the studied media, even at small concentrations.